ANTECEDENT OF SUPPLY CHAIN PERFORMANCE IN FMCG COMPANIES - Noah Bayu Abednego; Wahyuningsih Wahyuningsih; Triwulandari Dewayana (Jurnal Ekonomi, 2023)
This study aims to measure the effect of supply chain performance and share information on direct variables that affect supply chain performance in the fast moving consumers goods (FMCG) industry. The independent variables used are demand-side operational coordination, coordination of supply operational decisions, procurement digitalization, ability to analyze data, supply chain visibility, supply chain agility and supply chain collaboration. The sample in this study was 77 respondents from the logistics, warehouse, distribution, and supply chain divisions. The data analysis model used is the structural equation model (SEM). Therefore, this study examines demand-side operational coordination, coordination of supply operational decisions, procurement digitalization, ability to analyze data, supply chain visibility, supply chain agility and supply chain collaboration. Results this study is that there are several direct variables that have a positive influence on supply chain performance and there are also direct variables that have a negative influence on supply chain performance. The indicators in this study are adjusted to the criteria of the fast moving consumers goods (FMCG) business itself.